Cost‐containment in hypofractionated radiation therapy: a literature review. Issue 2 (13th March 2018) - Hunter, Darren; Mauldon, Emily; Anderson, Nigel
Abstract: Recent technological advances in radiation therapy have allowed for greater accuracy in planning and treatment delivery. The development of hypofractionated radiation treatment regimens is an example, and has the potential to decrease the cost per episode of care, relative to conventional treatments. Our aim was to analyse published literature on the cost‐effectiveness and budgetary implications of hypofractionated radiation therapy. As such, this article will quantify the projected health care cost savings and address the optimal means of treatment delivery, associated patient outcomes, and implications arising from an increased use of hypofractionated regimens. Abstract : This article provides an overview of the attributable Australian health care cost‐saving with an increase in hypofractionated radiation therapy. Within this context, issues pertaining to optimal treatment delivery method, treatment‐related outcomes and workforce sustainability are addressed.